PENYUSUNAN ANGGARAN PENJUALAN DAN ANGGARAN PRODUKSI UNTUK MAKSIMALISASI LABA PADA UMKM RUKUN DI BLITAR - Faizin, Erik Kustianto; Fahriani, Firda Zulfa (STKIP Persada Khatulistiwa Sintang, 2023)
UMKM are the business group with the largest number in Indonesia. The level of competition between business actors is also increasing. To face this competition, companies are required to be able to carry out proper planning so that the business activities carried out can continue and the main goal is to obtain maximum profits. The purposes of this study are (1) to analyze the preparation of the sales budget at Rukun UMKM in Blitar; (2) To analyze the preparation of the production budget for the Rukun UMKM in Blitar; (3) To analyze the preparation of the sales budget and production budget in maximizing profits at Rukun UMKM in Blitar. This research uses a qualitative approach with a descriptive research type. Data collection techniques using observation, interviews and documentation. the goal is to compile a sales budget and a production budget that are used to maximize profits at Rukun UMKM. The results of this study indicate that the 2023 sales budget is IDR 367.579.000 with a production level of 26,804 packs of Rukun tape candy which will generate a profit of IDR 150.216.512.